Investigating Speaking Anxiety in EFL Classrooms: A Case Study of Grade VIII Students - Mohammad Rey Gemilang; Sarlita D. Matra (FKIP, Universitas Palangka Raya, 2026)
Speaking anxiety remains a common challenge for students learning in EFL, often limiting their willingness to participate in oral classroom activities. This study explored the speaking anxiety experienced by eighth-grade students at SMP Negeri 10 Pekalongan, focusing on the forms of anxiety they encountered, the factors contributing to these experiences, and their influence on classroom participation. Using a qualitative case study approach, this research involved seven participants selected based on purposive sampling criteria. Evidence was obtained from classroom observations, semi-structured interviews, and questionnaires, then organized through coding before being interpreted using thematic analysis. The analysis showed that students' speaking anxiety was reflected in three closely related dimensions: communication apprehension, fear of negative evaluation, and low self-confidence. Students' speaking anxiety developed through the interaction of individual and classroom-related factors. Limited vocabulary and low self-confidence made students feel unprepared to speak, reactions of classmates and classroom atmosphere often increased their anxiety. Because of these conditions, many students became hesitant to speak and participated less in oral classroom activities.